Level of Cognitive Biases of Representativeness and Confirmation in Psychology Students of three Bío-Bío Universities - Castro M., Alexandra (2019)
Cognitive biases are unreasonable ways of making decisions, often in a one-sided way. The objective of this research was to describe the level of representativeness and confirmation biases in Chilean psychology students, in order to know how this phenomenon occurs. The participants were 198 psychology students from three universities in southern Chile. The instrument was based on two cognitive tasks derived from Kanheman and Tversky. The data were analyzed through descriptive statistics and mean differences. The results indicate a high level of biases in the groups of students, in the two tasks evaluated; the representativeness bias presents differences among universities only in sub-task 1, as well as in task 2, related to confirmation bias. Likewise, there are differences in representation bias according to age and sex. The need to strengthen reasoning skills in the initial training of future psychologists, in order to improve skills related to decision making in the professional field is concluded.